HRM 4.0 and New Managerial Competences Profile: The COMAU Case - Fregnan, Ezio; Ivaldi, Silvia; Scaratti, Giuseppe (Frontiers in Psychology, 2020)
The paper addresses the huge changes generated by the digital revolution, specifically focusing on the implications related to the HRM function. New challenges arise in dealing with digital work, digital employees and digital management, so that the connection between new technologies and HRM is described as electronic HRM (e-HRM).This entails the possibility to review of the notion of HRM examining new research perspectives and lines of interpretation following a Critical Management Studies approach, developing a more contextualized view in conceiving HRM, a more expansive consideration of stakeholders and a longer-term perspective in approaching the results of digital transformation and HRM outcomes.The paper analyses a specific organizational case, a multinational enterprise, exploring how the case study enhances the understanding of HRM as a social practice embedded in specific situated contexts.This enables the engagement of multiple rationalities, related to both internal and external stakeholders, overcoming a 'mere anti-performance stance' and achieving forms of reconstructive reflexivity about the interconnection between digital age, HRM and innovative generation of social value through an authentic corporate responsibility.